Внедрение программы реабилитации подростков 12-16-летнего возраста со сколиозом І-ІІ степени = Implementation of the program of rehabilitation Adolescents 12-16 years of age with scoliosis I-II degree - Tyagur, Taras (Journal of Education, Health and Sport, 2015)
Tyagur Taras. Внедрение программы реабилитации подростков 12-16-летнего возраста со сколиозом І-ІІ степени = Implementation of the program of rehabilitation Adolescents 12-16 years of age with scoliosis I-II degree. Journal of Education, Health and Sport. 2015;5(2):297-310. ISSN 2391-8306. DOI: 10.5281/zenodo.17868 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A297-310 https://pbn.nauka.gov.pl/works/561265 http://dx.doi.org/10.5281/zenodo.17868 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. Внедрение программы реабилитации подростков 12-16-летнего возраста со сколиозом І-ІІ степени Implementation of the program of rehabilitation Adolescents 12-16 years of age with scoliosis I-II degree Тарас Тягур Taras Tyagur Прикарпатский национальный университет имени Василя Стефаныка Vasyl Stefanyk precarpatian National University Резюме За последнее десятилетие сформировались негативные тенденции в динамике основных параметров здоровья подростков. Пристальное внимание к сколиозу объясняется тем, что при тяжелых формах данного заболевания и без своевременной коррекции деформации становятся фактором для развития структурных изменений в позвоночнике и заболеваний внутренних органов, что приводит к уменьшению продолжительности жизни и трудоспособности, а также и к инвалидности. Причины, которые могут привести к деформации, многочисленны. Негативное влияние оказывают неблагоприятные условия окружающей среды, социально-гигиенические факторы и длительное пребывание ребенка в неправильном положении тела. Рост числа детей со сколиозом в последние годы диктует необходимость разработки эффективных реабилитационных программ по лечению данной патологии. Для профилактики и коррекции сколиотической болезни наиболее эффективными средствами физической реабилитации считаются лечебная гимнастика и лечебно-оздоровительное плавание. Основные задачи физических упражнений сводятся к выработке правильной осанки, повышению силовой выносливости мышц, тренировке общей координации движений, что создает условия для восстановления правильного положения тела, исправления имеющихся дефектов, улучшения функции сердечнососудистой и дыхательной систем, общего оздоровления организма ребенка. Экспериментальная лечебная тактика сколиоза включала использование комплекса гидрокинезотерапии, дыхательную гимнастику Тай-Чи, подводное вытяжение и мануальную терапию. В контрольной группе была задействована классическая методика. Для установления эффективности разработанной методики было проведено антропометрическое исследованное, рассчитан индекс массы тела – ИМТ, изучены показатели вентиляционной функции легких и показатели сердечнососудистой системы. Улучшение физического статуса обследованных подростков со сколиозом I-II степени в рамках комплексной программы восстановительного лечения на этапе заключительного исследования проявлялось снижением нервно-психического напряжения, снижением количества жалоб, увеличением роста, веса и окружности груди, стабилизацией индекса массы тела (ИМТ), улучшением показателей дыхательной и сердечнососудистой системы. Разработанная комплексная программа коррекции заболевания является эффективным средством восстановительного лечения подростков со сколиозом I и II степени, поскольку положительная динамика в экспериментальной группе была более выражена по сравнению с традиционными методами лечения в контрольной группе. Ключевые слова: сколиотическая болезнь, деформация позвоночника, гидрокинезотерапия, плавание, физическая нагрузка, массаж, дыхательная гимнастика. Summary Over the last decade negative trend have formed in the basic parameters of adolescent health. Careful attention to scoliosis because severe forms of the disease, and without timely correction of the deformation becoming a factor for the development of structural changes in the spine and internal diseases, leading to reduced life expectancy and disability and disability. Causes that may lead to incorrect posture are numerous. Negative impact on the formation of posture have adverse environmental conditions, social and hygienic factors and long-term stay of the child in the correct position of the body. The growing number of children with scoliosis in recent years calls for the development of effective rehabilitation programs for the treatment of this disease. For the prevention and correction of posture the most effective means of physical rehabilitation are considered therapeutic exercises and therapeutic recreation swimming. The main objectives of physical exercise are reduced to develop the correct posture, increase muscle strength endurance, exercise overall coordination of movements, creates conditions for the restoration of the correct body position, correcting the defects, improving the function of the cardiovascular and respiratory systems, overall health of the child. Experimental scoliosis treatment tactics included the use of complex hydrokinesotherapy, breathing exercises of Tai Chi, underwater traction and manual therapy. The control group was involved in classical technique. To establish the effectiveness of the developed method was conducted anthropometric investigate calculated body mass index - BMI, studied indicators of pulmonary ventilation function and performance of the cardiovascular system. Improving the physical status of the surveyed adolescents with scoliosis I-II degree through an integrated program of rehabilitation treatment at the final stage of the study was shown a decrease in mental stress, decrease in the number of complaints, an increase of height, weight and chest circumference, stabilization of body mass index (BMI), improvements in respiratory and cardiovascular system. A comprehensive program of correction of the disease is an effective means of rehabilitation treatment of adolescents with scoliosis I and II degree, as a positive trend in the experimental group was more pronounced compared to the traditional methods of treatment in the control group. Key words: scoliosis, spinal deformity, hydrokinesiotherapy, swimming, exercise, massage, breathing exercises.